Discovery of gamma-and X-ray pulsations from the young and energetic PSR J1357-6429 with Fermi and XMM-Newton - Lemoine-Goumard, M.; Zavlin, V.; Grondin, M.; Shannon, Ryan; Smith, D.; Burgay, M.; Camilo, F.; Cohen-Tanugi, J.; Freire, P.; Grove, J.; Guillemot, L.; Johnston, S.; et al. (EDP Sciences, 2011)
Context. Since the launch of the Fermi satellite, the number of known gamma-ray pulsars has increased tenfold. Most gamma-ray detected pulsars are young and energetic, and many are associated with TeV sources. PSR J1357-6429 is a high spin-down power pulsar (E = 3.1 × 1036 erg s -1), discovered during the Parkes multibeam survey of the Galactic plane, with significant timing noise typical of very young pulsars. In the very-high-energy domain (E > 100 GeV), H.E.S.S. has reported the detection of the extended source HESS J1356-645 (intrinsic Gaussian width of 12') whose centroid lies 7' from PSR J1357-6429. Aims. We search for gamma-and X-ray pulsations from this pulsar, characterize the neutron star emission and explore the environment of PSR J1357-6429. Methods. Using a rotational ephemeris obtained with 74 observations made with the Parkes telescope at 1.4 GHz, we phase-fold more than two years of gamma-ray data acquired by the Large Area Telescope on-board Fermi as well as those collected with XMM-Newton, and perform gamma-ray spectral modeling. Results. Significant gamma-and X-ray pulsations are detected from PSR J1357-6429. The light curve in both bands shows one broad peak. Gamma-ray spectral analysis of the pulsed emission suggests that it is well described by a simple power-law of index 1.5 ± 0.3stat ± 0.3syst with an exponential cut-off at 0.8 ± 0.3 stat ± 0.3syst GeV and an integral photon flux above 100 MeV of (6.5 ± 1.6stat ± 2.3syst) × 10-8 cm-2 s-1. The X-ray spectra obtained from the new data provide results consistent with previous work. Upper limits on the gamma-ray emission from its potential pulsar wind nebula (PWN) are also reported. Conclusions. Assuming a distance of 2.4 kpc, the Fermi LAT energy flux yields a gamma-ray luminosity for PSR J1357-6429 of L ? = (2.13 ± 0.25stat ± 0.83 syst) × 1034 erg s-1, consistent with an L? E relationship. The Fermi non-detection of the pulsar wind nebula associated with HESS J1356-645 provides new constraints on the electron population responsible for the extended TeV emission. © 2011 ESO.